Growth Characteristics of Chikungunya Virus Isolate from Indonesia in Various Human Cell Lines in vitro - OKTAVIANI N. TURNIP; RAHMA F. HAYATI; RIZKA ALAWIYAH; BENEDIKTUS YOHAN; DIONISIUS DENIS; ANOM BOWOLAKSONO; AMIN SOEBANDRIO; R. TEDJO SASMONO; Oktaviani Naulita Turnip (Microbiology Indonesia, 2019)
Chikungunya (CHIK) fever, a febrile illness caused by Chikungunya virus (CHIKV) infection, is one of mosquito-borne viral diseases affecting people living in the tropical and subtropical regions in the world. The pathogenesis of the disease is yet to be completely unraveled, and research on CHIK has been conducted by employing various methods, including using cell lines to investigate the biological characteristics of CHIKV in vitro. To assess the suitability of human cell line model for CHIK study, various human cell lines including A549, Huh7, and HepG2 were infected with CHIKV and assayed for their susceptibility to infection. The MTT and plaque assay methods were performed to measure cell viability and virus growth kinetics, respectively. Fluorescence-activated Cell Sorting (FACS) and immunofluorescence assay were performed to measure the proportion of infected cells in the system and their morphological visualization. Both A549 and Huh7 human cell lines showed stable high cell viability upon infection while CHIKV growth kinetics were significantly lower in these cells compared to Vero-CCL81, a monkey cell line that is routinely used in other arboviruses research. Interestingly, we observed significantly different results in HepG2 human cell line, in which cell viability and CHIKV growth kinetics were significantly higher. FACS and immunofluorescence assay confirm the higher infection rate of CHIKV in HepG2 than A549 human cell line. We concluded herethat human hepatocytes HepG2 cell line was susceptible to Asian Genotype of CHIKV and proposed as an alternative cell for the in vitro CHIKV studies to the commonly used A549 and Vero cells.